Utilization of Chicken Feather Biomass As Metal Zinc Adsorbent (Zn2+) - Noer Hidayat, Djama’an; Maming, Maming; Liong, Syarifuddin (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Chicken feather is a waste that can be used as an alternative to adsorbents that can be used to overcome environmental pollution in waters containing heavy metal pollutants, especially on metal Zn (II) ions, Biomass Chicken Feathers using NaOH and Na2SO3 as adsorbent activation and proven using FTIR spectrophotometer . The metal adsorbent of Zn (II) ion by chicken feather biomass has been influenced to the variation of pH of the solution, mass of adsorbent, contact time, and concentration of chicken feather biomass. The method used is the method of "batch" and the metal concentration of Zn (II) ions measured by an atomic absorption spectrophotometer (AAS). Optimal variations that have been achieved under conditions of pH 6, adsorbent mass 0.7 gram, contact time for 80 minutes, and optimal concentration at 100 ppm with absorption of Zn (II) metal on chicken feather biomass of 6.04 mg/g. The metal adsorbent Zn (II) using chicken feather biomass is more in line with the Langmuir isothermal model with an adsorption capacity (Qo) value of 6.45 mg/g.